Fungal inhibiting capacity of an ethnobotanical plant from imugan, nueva vizcaya against Fusarium oxysporum and Fusarium moniliforme - Jacob, J. K. S.; David, E. S.; Undan, J. R. U. (International Journal of Agricultural Technology, 2016)
Ethnobotany pertains to the scientific association between people and plants. In the Philippines, many researches have been upraised to review the current ethnobotanical state and pharmacological properties of plants thriving for many indigenous tribes. One specific plant used by the Kalanguya tribe of the Northeastern Philippines is Derris elliptica, locally known as Derris elliptica, used as a fish poison, and only minor information was known about this indigenous plant’s taxonomy. This research was undertaken to evaluate the fungal-inhibiting capability of Derris elliptica against two fungal plant pathogens Fusarium oxysporum and Fusarium moniliforme. Hot water extracts of Derris ellipticaexhibited fungal inhibition to F. oxysporum as indicated by a retarded mycelial growth response (26.35 mm) compared to its negative control (70.07 mm) after five (5) days of incubation. The same observation was also exuded against F. moniliforme which also exhibited slow mycelial growth (28.28 mm) compared to the negative control (70.86 mm). Furthermore, hotwater extracts of D. elliptica can be considered as a fungal-inhibitor against these common plant pathogens comparable to commercially available fungal-inhibitory drugs and chemicals.